2020
DOI: 10.1080/0142159x.2020.1844877
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for the integration of medical students into telemedicine visits

Abstract: The use of telemedicine in clinical care has grown significantly in the last few years and has only increased during the COVID-19 pandemic. Given that many physicians will be expected to deliver virtual care moving forward, it is important for medical students to gain exposure via this modality during their clinical training. Many medical schools are actively working to integrate students into telemedicine. This article aims to provide guidance for readers incorporating medical students in telemedicine visits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
0
19
0
3
Order By: Relevance
“…Insight about the ways physicians adjusted during the expansion of telemedicine use, such as how they rapidly learned about and navigated the variety of telemedicine platforms (e.g., video, telephone, or patient portal), may help inform future efforts to support telemedicine implementation and use. Although ongoing telemedicine trainings may potentially reinforce these types of adjustments, 23 understanding the changes physicians have had to make to accommodate the increased use of telemedicine can also offer invaluable information about ways to improve the efficiency and effectiveness of care delivered through telemedicine. For instance, given our interviewees' enthusiasm about the use of messaging tools to rapidly share information with other physicians, our findings suggest it will be important to emphasize the opportunity for bidirectional communication to facilitate problem solving and knowledge sharing when using telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Insight about the ways physicians adjusted during the expansion of telemedicine use, such as how they rapidly learned about and navigated the variety of telemedicine platforms (e.g., video, telephone, or patient portal), may help inform future efforts to support telemedicine implementation and use. Although ongoing telemedicine trainings may potentially reinforce these types of adjustments, 23 understanding the changes physicians have had to make to accommodate the increased use of telemedicine can also offer invaluable information about ways to improve the efficiency and effectiveness of care delivered through telemedicine. For instance, given our interviewees' enthusiasm about the use of messaging tools to rapidly share information with other physicians, our findings suggest it will be important to emphasize the opportunity for bidirectional communication to facilitate problem solving and knowledge sharing when using telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Information technology experts may teach medics how to use various video-sharing platforms and to arrange networks for sharing audio-visual materials amongst researchers and educators with special interests [16]. Telemedicine has already been praised as a perspective area in rheumatology, orthopaedics, and rehabilitation amidst the COVID-19 pandemic [17,18,19].…”
Section: Online Survey Studiesmentioning
confidence: 99%
“…While clinical and practical aspects of the delivery of telemedicine have a stronger presence in the literature, education on delivery of video consultation is minimally represented. Prior to the pandemic only half of American medical schools included telemedicine in their curriculum [20] and since the pandemic there remains a gap in the literature in this area [21]. A single published systematic review from 2017 found only nine studies (published 2008-2014) relating to education and training in 'clinical telehealth' [22], many of which did not cover video consultation specifically in their training sessions.…”
Section: Introductionmentioning
confidence: 99%